Formation of CuOx Nanowires by Anodizing in Sodium Bicarbonate Solution - Damian Giziński; Anna Brudzisz; Mohammad Ramadan Alzahrani; Kuo-Kuang Wang; Wojciech Z. Misiołek; Wojciech J. Stępniowski (Crystals, 2021)
Mechanism of copper nanostructuring by oxides and hydroxide formation during anodizing is not fully understood. At the same time, the search for novel copper anodizing regimes and electrolytes is ongoing due to multiple potential applications. In this work copper anodizing in two electrode setups, in stirred 0.01 M solution of NaHCO3 at 20 °C and at voltages ranging from 5 to 40 V was explored. The morphology and composition of prepared materials were studied using FE-SEM imaging and XRD measurements. Anodizing at potentials in a range of 15–30 V led to formation of nanowires composed of crystalline Cu2O, CuO, Cu(OH)2 and malachite Cu2CO₃(OH)2. The latter was formed due to anion incorporation from the electrolyte. The diameter of nanowires strongly depended on the applied voltage, and was 35 ± 6 nm for samples prepared at 15 V, and 45 ± 9 nm for 30 V. At higher applied voltages oscillations of current density were observed, suggesting partial delamination of the formed oxidized layer, with subsequent self-healing.